2003
DOI: 10.1002/aoc.427
|View full text |Cite
|
Sign up to set email alerts
|

Use of 111In–L–LDL radiotracers to detect human pancreatic and mice melanoma tumors

Abstract: The present study was designed to evaluate the potential of labeled low-density lipoprotein with 111 In using a lipid chelating agent (bis(stearylamide) of diethylenetriaminepentaacetic acid: L) to detect pancreatic tumors and melanoma in mice by gamma-scintigraphy. We compare the biodistribution of radioactivity and scintigraphic images in nude mice heterotransplanted with human cancerous pancreatic duct cells (Capan-1) and in mice transplanted with murine tumor cells (B16 melanoma). Biodistribution studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a previous study, we suggested that the ability of 111 In-L-LDL tracers to detect human pancreatic tumors by scintigraphy depended on the degree of vascularization of the tumor. 18 To support this interpretation, we investigated strongly vascularized pancreatic xenografts. Various cancerous human pancreatic lineages maintained in vitro have been heterotransplanted into nude mice to determine the extent of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we suggested that the ability of 111 In-L-LDL tracers to detect human pancreatic tumors by scintigraphy depended on the degree of vascularization of the tumor. 18 To support this interpretation, we investigated strongly vascularized pancreatic xenografts. Various cancerous human pancreatic lineages maintained in vitro have been heterotransplanted into nude mice to determine the extent of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 This was accounted for by weak angiogenesis after heterotransplantation into nude mice of Capan-1 cells in contrast to the strong angiogenesis observed in xenografts of human melanoma cells. 18 Here, we present results in favor of this hypothesis using cancerous pancreatic cells of the AR4-2J line heterotransplanted into nude mice. These xenografts of rat origin are strongly vascularized in this host.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation